Modeling the Risk Level of Information Security at Enterprise - Hladka, Olena Mykolayivna; Karpovych, Ivan Mykolayovich; Nakonechnа Juliya (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
The paper is devoted to the study of cybersecurity of information resources at an enterprise. We consider some of the methods that allow you to analyze information security risks and evaluate the optimal costs for an enterprise to protect information. Addressing the cybersecurity problem of information resources requires the preparation and adoption of organizational and technical measures, the development of which is based on the approaches proposed.